Portable Pocket Printer - AL Imprimeur Sdn. Bhd / Nurul Natasha Hairul Anuar - Hairul Anuar, Nurul Natasha (2020)
This is an entrepreneur project that has been carried out in some situation to make an innovation implemented by students in UiTM Cawangan Negeri Sembilan. This is a subject which everybody have to undergo a new product development assignment for students who take ENT600 subject. In the first part of the task report, the general data of the business enterprise has been collected. Information is gathered via the primary data and also through questionnaire survey then they will make some innovation on certain products and presenting them. In order to enjoy an easier lifestyle, it is complementary to have a printer especially for students and employees which this product can help them to complete and have soft copy for all their works and tasks. Those appliances is important so that, students and employees can finish their works and task without faced any problems or difficulties. But, there is some problem faced by them which printer cannot easily carry because printer is quite heavy and it cannot be bring anywhere because it requires power supply to be used.